Reversine inhibits MMP-3, IL-6 and IL-8 expression through suppression of ROS and JNK/AP-1 activation in interleukin-1β-stimulated human gingival fibroblasts. (December 2019) - Song, Hyun-Kyung; Noh, Eun-Mi; Kim, Jeong-Mi; You, Yong-Ouk; Kwon, Kang-Beom; Lee, Young-Rae
Highlights: Reversine inhibits IL-1β-induced MMP-3, IL-6, and IL-8 expression. Reversine suppresses IL-1β-induced ROS generation. Reversine inhibits IL-1β-stimulated JNK MAP Kinase and AP-1 activation. Abstract: Objective: Periodontitis is an inflammatory disease of the supporting tissue around teeth commonly caused by gram-negative bacterial infections. Interleukin (IL)-1β, a cytokine involved in host immune and inflammatory responses, is known to induce the activation of various intracellular signaling pathways. One of these signaling mechanisms involves the regulation of gene expression by activation of transcription factors (AP-1 and NF-κB). These transcription factors are controlled by mitogen-activated protein kinases (MAPKs), which increase cytokine and matrix metalloproteinase (MMP) expression. We examined the preventive effects of reversine, a 2, 6-disubstituted purine derivative, on cytokine and MMP-3 expression in human gingival fibroblasts (HGFs) stimulated with IL-lβ. Study design: Western blot analyses were performed to verify the activities of MAPK, p65, p50, and c-Jun and the expression of MMPs in IL-1β-stimulated HGFs. Cytokine and MMP-3 expression in IL-1β-stimulated HGFs was measured by real-time quantitative polymerase chain reaction. Results: Reversine decreased the IL-1β-induced expression of proinflammatory cytokines (IL-6 and IL-8) and MMP-3 in HGFs. Furthermore, the mechanism underlying the effects of reversine involved the suppression of IL-1β-stimulated MAPK activation and AP-1 activation. Conclusion: Reversine inhibits IL-1β-induced MMP and cytokine expression via inhibition of MAPK/AP-1 activation and ROS generation. Therefore, we suggest that reversine may be an effective therapeutic candidate for preventing periodontitis.